Infográfico para prevenção dos transtornos mentais menores da equipe de enfermagem antes e durante a fase de desaceleração profissional - Franco, Suzicléia Elizabete de Jesus (2024)
Introduction: Nursing workers have different phases that can be directly related to their behavior towards the profession, considered as before the professional slowdown, during the professional slowdown and retirement. The penultimate stage is characterized by the selective search to remain in activities and jobs that ensure the worker's retirement, a stage in which many nursing professionals verbalize feelings such as insecurity, anxiety and fear of withdrawing from the world of work, as well as from the social interaction provided by the work environment, factors that can contribute to mental illness. Objective: To create an infographic for the prevention of minor mental disorders among nursing staff before and during the professional slowdown phase. Methodological procedures: This is a methodological study, focusing on nursing workers in an Emergency Care Unit who are before and during the professional deceleration phase. The study was conducted in three different stages, namely: 1) the preparation of an integrative review; 2) a survey of the personal and occupational factors associated with Minor Mental Disorders among the nursing staff of the Emergency Care Unit before and during the professional deceleration phase; and 3) the construction of an educational technology, of the infographic type. The quantitative data was analyzed using the SPSS 25.0 software, using descriptive analysis and the Chi-square/Fisher's exact test, considering p=<0.05. The risk was estimated using the Odds Ratio. Content analysis was applied to the data from the production of the infographic. Results: The integrative review resulted in 1,901 articles, eight of which made up the final sample. The field research revealed that 43% of nursing professionals had Minor Mental Disorders. As for the personal, psychosocial and occupational factors associated with Minor Mental Disorders among the nursing staff (n=35), the following stand out: schooling (high school), having a religion, having a good perception of their state of health (physical and mental), having social support, being in a phase of professional deceleration, having taken vacation in the last 12 months and feeling motivated at work all contributed to reducing the chances of Minor Mental Disorders by 32.3%, 48.4%, 59.9%, 17.2%, 7.7%, 26.6% and 39.1% respectively. On the other hand, being male, being white, having an income of up to 4 minimum wages, having children, having anxiety, having suffered psychological and emotional violence at work and working the day shift increased the chances of developing Minor Mental Disorders by 17.9%, 27.8%, 80.6%, 62.5%, 80.6%, 4.3% and 26.3% respectively. Final considerations: The nursing team presented factors that can contribute to mental illness, which reveals the need for strategies aimed at caring for the health of this profile of worker. The infographic developed, as an educational technological product in health, proved to be valid for use in this population, containing playful information, focused on self-care and which can contribute to the prevention of Minor Mental Disorders in nursing staff.